"Stoma or no stoma": First report of intestinal transplantation without stoma. Issue 12 (23rd June 2020) - Moon, Jang I.; Zhang, Hongbin; Waldron, Levi; Iyer, Kishore R.
Abstract : Recent data suggest that frequent endoscopy and biopsy without evidence of graft dysfunction does not appear to confer survival advantage after intestinal transplantation. After abandoning protocol surveillance, endoscopic examination was decreased significantly at our center. These observations led us to question the need for stoma creation in intestinal transplantation. Herein, we report clinical outcomes of intestinal transplantation without stoma, compared to conventional transplant with stoma. Data analysis was limited to adult intestinal transplantation without liver allograft between 2015 and 2018. We compared patient and graft survival, frequency of endoscopic evaluation, episodes of acute rejection, nutritional therapy, and renal function between "Control group (with stoma), " n = 18 grafts in 16 patients and "Study group (without stoma), " n = 16 grafts in 15 patients. Overall outcome was similar between the 2 groups with respect to graft and patient survival, episodes of acute rejection, and its response to treatment. Nutritional outcomes were similar in both groups. Fewer antidiarrheal medications were required in the study group, but this did not translate into demonstrable gains in preservation of renal function, despite an apparent trend to improvement. Intestinal transplantation without stoma appears to be an acceptable practice model without obvious adverse impact on outcome. Abstract : A comparison of intestinal transplant recipients with and without ostomy shows comparable graft and patient survival, rejection rate, and rejection treatment response.